SISTEM SMART FARM BERBASIS IOT MENGGUNAKAN NODEMCU PADA PETERNAKAN AYAM KAMPUNG - Sandi Yoni Saputra; Dendy Kurniawan; Iman Saufik Suasana; Ahmad Ashifuddin Aqham; Edy Siswanto (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Native chicken farming plays an essential role in supporting community food supply, particularly as a source of animal protein. However, feeding activities and feed stock management are still commonly performed manually, resulting in high labor requirements and time consumption. inconsistent feeding schedules, and inadequate monitoring of feed availability, which may negatively affect farm productivity. This study aims to design and implement an Internet of Things (IoT)-based smart farm system that enables automatic feeding and real-time monitoring of feed stock for native chicken farming. The system utilizes an ESP32 microcontroller as the main control unit, a servo motor to regulate feed distribution, an HC-SR04 ultrasonic sensor to measure feed levels, and a Real Time Clock (RTC) module to manage feeding schedules. All system information and feed stock status are transmitted directly to farmers through the Telegram application using a Bot API. The research method applied in this study is Research and Development (R&D) using a prototyping approach, which consists of requirement analysis, system design, prototype development, testing, and implementation. The results demonstrate that the developed system can operate automatically according to predefined schedules and provide timely notifications when feed stock reaches a critical level. The implementation of this system improves operational efficiency, reduces manual workload, and supports better management of native chicken farming through the use of IoT technology.